THE ORIGIN OF ABYSSAL PERIDOTITES: A NEW PERSPECTIVE - Niu Y.; Langmuir C.H.; Kinzler R.J. (My University, 1997)
Abyssal peridotites have been interpreted to be residues of mantle melting beneath ocean ridges. Recent experimental data and models of mantle melting allow quantitative tests of this hypothesis. The tests show that abyssal peridotites are not purely melting residues. Their modal proportions and whole-rock compositions have far more olivine than would be predicted from melting models. Nonetheless, the correlations between modal proportions of olivine and residual mineral chemistry, and the relationship between associated basalt and peridotite compositions, require an important role for melting. We suggest that abyssal peridotite compositions result from a combination of melting and crystallization processes that are both a natural response to ascent of solid and melt beneath an ocean ridge. Different extents of melting create a range of residual peridotite and mantle melt compositions. The buoyant melts migrate upwards, where they encounter the surface thermal boundary layer and crystallize olivine. The greater the ambient extent of melting of the mantle, the higher the normative olivine contents of the melt, and the more melt is produced. Hence greater extents of melting lead to more olivine crystallization at shallow levels. This correlation between melting and crystallization within the mantle preserves the observed relationships between peridotite modes and mineral compositions. Significant implications of these results are: (1) the bulk composition of the oceanic crust differs from the primary melt compositions produced by partial melting of the mantle because of olivine crystallization at the thermal boundary layer; (2) the actual thickness of igneous crust may be variably thinner than would be calculated assuming total melt extraction; and (3) peridotite modes can be used to infer polybaric mantle melting reactions only if the accumulated olivine is removed appropriately.
Keywords: PERIDOTITES; MID-OCEAN RIDGE BASALTS; MANTLE; PARTIAL MELTING; MID-OCEAN RIDGES